ANALISIS KETIMPANGAN WILAYAH DAN PERTUMBUHAN EKONOMI ANTARA KABUPATEN INDUK DAN PEMEKARANNYA DI PROVINSI ACEH - Sulasmi Sulasmi; M. Ilhamsyah Siregar (Fakultas Ekonomi dan Bisnis UNSYIAH, 2020)
AbstractThis study aims to determine regional inequality and economic growth in the parent district and its provision in Aceh Province. This research uses a descriptive quantitative approach. Research data used in 2010-2018. The analysis used is the Williamson Index and Klassen Typology. The results show that Lhokseumawe City has the highest per capita GRDP, while the highest economic growth is in West Aceh District. The results of the calculation of regional inequality explained that in region 1 with the central district of West Aceh showed an inequality rate of 0.28 but decreased not far in 2018 of 0.27. Shallow categories of regional inequality are found in regions three, five, seven, and eight. The results of the Klassen Typology clarification explained that Aceh Barat Daya, Gayo Lues, and Lhokseumawe are fast-growing and fast-advancing areas. Meanwhile, Simeulue, Aceh Jaya, Singkil, Bener Meriah, and Pidie Jaya are relatively disadvantaged areas.Keywords: GRDP per Capita, Economic Growth, Regional Inequality, Klassen Typology